804 Using Simulation as A Platform to Prepare for ENT Emergencies in The COVID-19 Era. (4th May 2021) - Li, L; Hopkins, M; Oliver, N; Wet, D T Du; Hathorn, I; Mellanby, E
Abstract: Introduction: At the onset of COVID-19 crisis, our ENT department was allocated five interim foundation (FiY1) doctors to help support the clinical team at a time of extreme pressure within the NHS. An ENT emergency simulation programme was-established in order to improve the skills, knowledge and confidence of the new doctors, with the course being subsequently incorporated into departmental induction for the new first-on-call-ENT-doctors. Method: Five FiY1 doctors attended a simulation study day, comprised of a "skills and drills" workshop followed by two interactive scenarios. An interactive SimMan3G-mannequin, technician utilizing a Mask-Ed™, trained confederate nurse and a video flexible laryngoscope trainer were used to provide high-fidelity simulation. Participants rated how prepared-they felt in managing the relevant condition before and after on a Likert scale (1–strongly disagree, 5–strongly agree). The session was repeated for the new nine first-on-call ENT doctors. Results: Participants in the pilot session felt more prepared in managing both tracheostomy emergencies (1.2vs4.2)-and-epistaxis (2.0vs5.8). Participants in the subsequent session also felt-more-prepared in managing stridor (2.1vs4.6) -and-epistaxis-(3.1vs4.7). All-14-attendants stated that they would recommend the session to others. Conclusions: Despite-the-simulation-course-being-originally-established-to help support newly qualified-FiY1 doctors during COVID-19, the success of the programme has resulted in its formal incorporation-into departmental ENT induction.